Causal relationships between CD25 on immune cells and hip osteoarthritis - Luo, Hao; Zhu, Yong; Guo, Bin; Ruan, Zhe; Liu, Zhi; Fan, Zhihua; Zhao, Shushan (Frontiers in Immunology, 2023)
Previous research has indicated a potential association between immune factors and osteoarthritis (OA), but the causal relationship between CD25 expression on immune cells and hip OA remains enigmatic. To shed light on this relationship, this study utilized the two-sample Mendelian Randomization (MR) method. Leveraging genome-wide association studies (GWAS) data from the UK Biobank and arcOGEN, the investigation encompasses a substantial European cohort comprising 15,704 hip OA cases and 378,169 controls. Genetic insights into CD25 stem from a subgroup of 3,757 individuals with European ancestry, encompassing 77 CD25-related traits. Several MR methods were applied, and robustness was assessed through heterogeneity and sensitivity analysis. Among the 77 traits examined, 66 shared the same single nucleotide polymorphisms (SNPs) with hip OA. Of these, 7 CD25-related traits were found to be causally associated with hip OA (adjusted P<0.05), with F-statistics ranging from 33 to 122. These traits are specifically related to CD4+CD25+ T cells, exhibiting odds ratios (OR) and 95% confidence intervals (CI) less than 1. Notably, no causal link was discerned with the CD8+CD25+ T cell subset. Within absolute count (AC) and relative count (RC) trait types, a significant causal relationship was observed solely between CD4+CD25+ T cells and hip OA, without subtype localization. A more intricate examination of CD25 expression levels within the CD4+CD25+ T cell subset revealed a correlation with the CD39+ regulatory T (Treg) subset and hip OA, particularly within the CD39+ activated Treg subset. Furthermore, a notable causal relationship emerged between CD25 expression levels in the CD45RA- not Treg subset and hip OA. However, no significant causal link was established with any subsets of B cells. The genetic prediction suggests that CD25, particularly within the realm of CD4+CD25+ T cells, may exert a protective influence against the development of hip OA. These findings provide a novel therapeutic approach for the prevention and treatment of hip OA.